The chemistry of imidazoles and pyrimidinones - Hannah, Duncan Robert (1997)
The reactions of amino- and formylimidazoles, and aminopyrimidinones are described. Conditions were found for the successful condensation of 5(4)-aminoimidazole-4(5)-carboxamide with a number of substituted benzaldehydes, to provide a series of novel 5(4)-N-benzylideneaminoimidazole-4(5)-carboxamides. Reaction of a subset of the benzylidene derivatives with sodium hydride furnished novel imidazo[1,5-a]quinazoline-3-carbox-amides in good yields, via an intramolecular cyclisation. Attempted mixed acid nitration of imidazo[1,5-a]quinazoline-3-carboxamide led only to amide hydrolysis to provide the carboxylic acid. High yielding conditions were sought for the synthesis of a formylimidazole by the selective partial reduction of commercially available 4,5-disubstituted imidazoles. Lithium triethoxy-aluminium hydride reduction of 1-benzyl-4,5-dicyanoimidazole gave a mixture of the isomeric monoaldehydes in a yield of 53%. Methyl 5(4)-formylimidazole-4(5)-carboxylate was formed by acidic hydrolysis of methyl 5(4)-diethoxymethylimidazole-4(5)-carboxylate. Unfortunately, Knoevenagel condensation of the formyl-imidazoles prepared with ethyl nitroacetate could not be achieved. Ethoxycarbonylacetylferrocene and 1,1'-bis(ethoxycarbonylacetyl) ferrocene, prepared from ferrocene in one and two steps respectively via Friedel-Crafts acylations, were heated with guanidine carbonate to provide 1-(2-amino-3,4-dihydro-4-oxopyrimidin-6-yl)ferrocene and 1,1'-bis(2-amino- 3,4-dihydro-4-oxopyrimidin-6-yl)ferrocene in low yields, though the latter appeared to decompose on storage. In studies aimed at preparing a pyrimido[5,4-b]indole, attempted nitrosation of 2-amino-6-phenylpyrimidin- 4-one with nitrosonium tetrafluoroborate gave the unexpected unsymmetrical dimer 2-amino -5-(3,4-dihydro-4-oxo-6-phenylpyrimidin-2-yl)-6-phenylpyrimidin-4-one, in low yield. To overcome the observed poor reactivity of 2- amino-5-halopyrimidin-4-ones towards Suzuki coupling with boronic acids, 2-amino-5-halo-4-methoxy-6-phenylpyrimidines were prepared and successfully coupled with a range of aryl and heteroaryl boronic acids to provide 5-aryl-and 5-heteroarylpyrimidines in good to excellent yields. As expected, the iodopyrimidine was more reactive to the palladium catalysed coupling than the bromo analogue. Acidic hydrolysis of the 5-arylpyrimidines furnished 2- amino-5-aryl-6-phenylpyrimidin-4-ones in excellent yields. Heck reactions of 2-amino-5-iodo-6-phenylpyrimidin-4-one and 1-hexyne gave only a low yield of 6-amino-2-butyl-4-phenylfuro[2,3-d]pyrimidine, involving intramolecular cyclisation. Unlike the trend observed for Suzuki reactions, Heck reaction of 2-amino-5-iodo-4-methoxy-6-phenylpyrimidine with 1-hexyne gave the coupled product, 2-amino-5-(1-hexyn-1-yl)-4-methoxy-6-phenylpyrimidine, but only in a low yield of 27%.